Restructuring Highway Agencies - The FinnRa Case : Options for Africa? - Ojala, Lauri; Sirvio, Esko (World Bank, Washington, DC, 2012)
Until the late 1970s, the Finnish Road and Waterways Administration (RWA), under Finland's Ministry of Transportation and Communications (MOTC), operated as a highly centralized, monopolistic agency. The country's thirteen road management districts had little or no decision-making authority. Outsourcing construction works was limited, contracting maintenance services was rare, and RWA often implemented its road construction projects using in-house labor and rented machinery and vehicles. Following the oil crisis of 1974, public resources were constrained and road expenditure was targeted at maintenance rather than at new construction. Simultaneously, RWA's focus shifted to construction management (rather than actual execution of works) and to maintenance activities. Outsourcing of planning, design, and construction services became more prevalent. New, more user-friendly procurement procedures were introduced, facilitating the use of private small contractors. This trend continued through the 1980s, when individual road districts assumed the practice of slicing up the procurement of works into sufficiently small contracts to allow small regional-based contractors to bid for them.